Care leavers on social work courses: a study of identity management. Issue 1 (30th July 2015) - Ward, Simon; Devereux, Rose; Mayall, Helen; O'Neill, Teresa; Worsley, Aidan
Abstract: Care leavers constitute a small but important minority of social work students. Their dual role as previous 'consumers' of care and students is of inherent interest to both those involved in social work education and providers of social work services. This paper discusses a small research project that explored the experiences of such students through semi‐structured interviews. One theme that reoccurred in the analyses of the interview transcripts was how the students managed their identities, through the time that they were in care, in the period having left care and having been accepted on a social work course. What the interviewees had to say about their care and subsequent life experiences is worthy of consideration in terms of its implications for the delivery of social work education generally and how care leavers on social work courses should be treated by academics and on placement particularly.